Analisis tantangan, strategi dan digitalisasi UMKM F&B dalam meningkatkan competitive advantage: Pendekatan systematic literature review - Alean Kistiani Hegy Suryana; Muzakar Isa; Kussudyarsana Kussudyarsana (Nur Science Institute, 2026)
This study aims to identify the main challenges and strategies for enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage (F&B) sector through a Systematic Literature Review (SLR). The methodology involved a literature search in the Scopus database using inclusion criteria such as relevance, publication within the last 10 years, and peer-reviewed status. From 18 selected articles, thematic analysis was conducted to identify recurring patterns related to MSMEs’ competitiveness. The analysis revealed three dominant thematic challenges, including limited organizational capacity, digital inertia, and low green readiness, which constrain MSMEs’ ability to adapt, innovate, and sustain competitive performance. The findings show that MSMEs face barriers such as weak managerial capabilities, supply chain vulnerabilities, and slow adoption of digital and sustainability practices. Recommended strategies include managerial capability development, supply chain strengthening, digital adoption, and sustainability integration.